Radiology Reporting in the Era of Patient-Centered Care: How Can We Improve Readability? - Patil, Siya (J Digit Imaging, 2021)
Radiology reports are consumed not only by referring physicians and healthcare providers, but also by patients. We assessed report readability in our enterprise and implemented a two-part quality improvement intervention with the goal of improving report accessibility. A total of 491,813 radiology reports from ten hospitals within the enterprise from May to October, 2018 were collected. We excluded echocardiograms, rehabilitation reports, administrator reports, and reports with negative scores leaving 461,219 reports and report impressions for analysis. A grade level (GL) was calculated for each report and impression by averaging four readability metrics. Next, we conducted a readability workshop and distributed weekly emails with readability GLs over a period of 6 months to each attending radiologist at our primary institution. Following this intervention, we utilized the same exclusion criteria and analyzed 473,612 reports from May to October, 2019. The mean GL for all reports and report impressions was above 13 at every hospital in the enterprise. Following our intervention, a statistically significant drop in GL for reports and impressions was demonstrated at all locations, but a larger and significant improvement was observed in impressions at our primary site. Radiology reports across the enterprise are written at an advanced reading level making them difficult for patients and their families to understand. We observed a significantly larger drop in GL for impressions at our primary site than at all other sites following our intervention. Radiologists at our home institution improved their report readability after becoming more aware of their writing practices.